The international experience of in-situ recovery of the DCD heart: a multicentre retrospective observational study. (April 2023) - Louca, John; Öchsner, Marco; Shah, Ashish; Hoffman, Jordan; Vilchez, Francisco González; Garrido, Iris; Royo-Villanova, Mario; Domínguez-Gil, Beatriz; Smith, Deane; James, Leslie; Moazami, Nader; Rega, Filip; et al.
Summary: Background: Heart transplantation is an effective treatment offering the best recovery in both quality and quantity of life in those affected by refractory, severe heart failure. However, transplantation is limited by donor organ availability. The reintroduction of heart donation after the circulatory determination of death ( DCD ) in 2014 offered an uplift in transplant activity by 30%. Thoraco-abdominal normothermic regional perfusion (taNRP) enables in-situ reperfusion of the DCD heart. The objective of this paper is to assess the clinical outcomes of DCD donor hearts recovered and transplanted from donors undergoing taNRP. Method: This was a multicentre retrospective observational study. Outcomes included functional warm ischaemic time, use of mechanical support immediately following transplantation, perioperative and long-term actuarial survival and incidence of acute rejection requiring treatment. 157 taNRP DCD heart transplants, performed between February 2, 2015, and July 29, 2022, have been included from 15 major transplant centres worldwide including the UK, Spain, the USA and Belgium. 673 donations after the neurological determination of death (DBD) heart transplantations from the same centres were used as a comparison group for survival. Findings: taNRP resulted in a 23% increase in heart transplantation activity. Survival was similar in the taNRP group when compared to DBD. 30-day survival was 96.8% ([92.5%–98.6%] 95% CI, n = 156), 1-year survival was 93.2% ([87.7%–96.3%] 95% CI, n = 72) and 5-year survival was 84.3% ([69.6%–92.2%] 95% CI, n = 13). Interpretation: Our study suggests that taNRP provides a significant boost to heart transplantation activity. The survival rates of taNRP are comparable to those obtained for DBD transplantation in this study. The similar survival may in part be related to a short warm ischaemic time or through a possible selection bias of younger donors, this being an uncontrolled observational study. Therefore, our study suggests that taNRP offers an effective method of organ preservation and procurement. This early success of the technique warrants further investigation and use. Funding: None of the authors have a financial relationship with a commercial entity that has an interest in the subject.